MOOCs and OER in the Global South: Problems and Potential - King, Monty; Pegrum, Mark; Forsey, Martin (The International Review of Research in Open and Distributed Learning, 2018)
This paper examines the problems and potential of Massive Open Online Courses (MOOCs) and Open Education Resources (OER) in the global South. Employing a systematic review of the research into the use of open online learning technologies in Southern contexts, we identify five interrelated themes emerging from the literature: 1) access to the Internet; 2) participant literacies; 3) online pedagogies; 4) the context of content; and 5) the flow of knowledge between North and South. The significance of Southern voice and participation is addressed in the final section, which concludes that on balance, the literature offers a qualified endorsement of the potential and actualities of MOOCs and OER in the global South. The ongoing tendency for the research literature to pay little heed to the agency of the social actors with the most to gain from these innovations is noted, opening up space for further research into the lived experience of online learners in the global South.
Keywords: __C:filed:1